LITERATURE REVIEW: IOT-BASED GEOGRAPHIC INFORMATION SYSTEM FOR MONITORING SOIL CHEMICAL PROPERTIES IN OIL PALM PLANTATIONS - Banyuriatiga, Banyuriatiga; Sari, Kartika; Syaddam, Syaddam; Rahman, Arief; Adlian, Adlian (Universitas Muria Kudus, 2025)
Oil palm has a crucial role in the National economy, where its productivity depends on the soil chemical properties of the soil. In practice, monitoring methods carried out using conventional methods can be time-consuming and expensive. Therefore, a more efficient approach is needed. By reviewing previous research, this study highlights the latest developments, challenges, opportunities, and future directions in utilising the Internet of Things and Geographic Information Systems for monitoring soil chemical properties in oil palm plantations, thereby supporting more productive and sustainable management. The descriptive method was applied in this literature review research to 26 relevant articles selected from various publication databases, covering the time frame from 2020 to 2024. This study examines the development of IoT sensors for monitoring soil parameters, including humidity, pH, and temperature, in real-time, as well as the application of GIS for spatial analysis and data visualization. The results highlight the significant potential of integrating IoT and GIS to provide efficient real-time data and spatial analysis, thereby supporting more precise land management and informed decision-making, particularly concerning soil fertility and fertilizer use.